IMPACT OF DELAYED CRUSH ON POST-HARVEST DETERIORATION OF PROMISING EARLY MATURING SUGARCANE CLONES - REDDY, Y. SHARATH KUMAR; MADHURI, K. V. NAGA (The Bioscan, 2014)
Sugarcane is a perishable commodity and must be processed in to sugar quickly after it is harvested. Post harvest sucrose losses have been reported from many cane producing countries due to delayed crushing as a major concern. In this context to access the effect of delayed crushing in sugarcane the present study was conducted with seven promising early maturing sugarcane clones at Agricultural Research station, Perumallapalle, A.P., India during Rabi 2011-2012. Different biochemical aspects like percent juice sucrose, TSS, commercial cane sugar percent, reducing sugars %, juice pH & juice extraction percent were assayed from 0-120 hrs at 24 hrs interval after harvest to identify the sugar cane clones suitable for delayed crushing. The results of the study indicated that the clones 2006T36 and 2006T3 recorded highest sucrose% (16.37%,15.18%) and lowest reducing sugars (2.50%,2.70%) respectively and were found to posses tolerance to post harvest deterioration. While the clone 2006T23 recorded highest reducing sugars (3.72%) and lowest sucrose % (12.39%) indicating the deterioration in quality. However, significantly highest cane yield was recorded in Co C 671 (1.64 kg), Co 94008 (1.42 kg) and 2006T36 (1.49 kg).